ICOS ATC/CAL Flask Release from Norunda (100.0 m), 2019-11-12–2026-01-16 - Irene Lehner; Meelis Molder (Integrated Carbon Observation System, 2026)
can contain atmospheric composition data for any of a number of gases; the data can be a mole fraction, isotope ratio, or other related quantity
Lehner, I., Molder, M. (2026). ICOS ATC/CAL Flask Release from Norunda (100.0 m), 2019-11-12–2026-01-16, ICOS RI, https://hdl.handle.net/11676/KXyV35_lSpl0-jGEy6fE0DDd
Keywords: Atmosphere Thematic Centre; Flask; ICOS; time instant, UTC; time instant, UTC; δ13C-CO2; δ13C-CO2; standard deviation; standard deviation; number of points; number of points; quality flag; quality flag; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap